1972
DOI: 10.1073/pnas.69.4.993
|View full text |Cite
|
Sign up to set email alerts
|

Long-Lived Conformation Changes Induced by Electric Impulses in Biopolymers

Abstract: Electric impulses are capable of inducing long-lived conformational changes in (metastable) biopolymers. Results of experiments with poly(A) 2 poly(U) and ribosomal RNA, which are known to develop metastabilities, are reported. A polarization mechanism is proposed to explain the structural transitions observed in the biopolymers exposed to the impulses. In accordance with this idea, the applied electric field (of about 20 kV/cm and decaying exponentially, with a decay time of about 10 $sec) induces large dipol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

1972
1972
2017
2017

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 141 publications
(28 citation statements)
references
References 13 publications
0
27
0
1
Order By: Relevance
“…Dielectric measurements have shown that polypeptides in viscous organic solvents may undergo intramolecular helix-coil transitions in the presence of electric fields (Schwarz and Seelig, 1968). In the meantime there are many reports on fieldinduced conformational chanoes in multi-stranded as well as in single-stranded polyelectrolytes (Neumann and Katchalsky, 1972;Neumann, 1973;Kikuchi andYoshioka, 1973, 1976;Yasunaga et al, 1973;Revzin and Neumann, 1974;Prrschke, 1974Prrschke, , 1976Prrschke, , 1985.…”
Section: Biopolymersmentioning
confidence: 99%
“…Dielectric measurements have shown that polypeptides in viscous organic solvents may undergo intramolecular helix-coil transitions in the presence of electric fields (Schwarz and Seelig, 1968). In the meantime there are many reports on fieldinduced conformational chanoes in multi-stranded as well as in single-stranded polyelectrolytes (Neumann and Katchalsky, 1972;Neumann, 1973;Kikuchi andYoshioka, 1973, 1976;Yasunaga et al, 1973;Revzin and Neumann, 1974;Prrschke, 1974Prrschke, , 1976Prrschke, , 1985.…”
Section: Biopolymersmentioning
confidence: 99%
“…In such systems the electric impulse is capable of shifting the ionic atmosphere relative to the associated polyanions. The displacement of the screening counterions causes increased electrostatic repulsion between the polyanions and leads to partial complex dissociation (Neumann & Katchalsky, 1972).…”
Section: Polarization Mechanismmentioning
confidence: 99%
“…1 The amount of AcCh in the storage form is then given by the following expression: d(AcChs)/dt = Tm-'(AcChp) -rl-'(AcChs) [10] while that bound to the receptor is: d(AcChf)/dt = -r2-'(AcChf) + rl-'(AcChl) [11] Moreover, the rate of liberation of (AcChs) and (Caf) from their bound form are field-dependent because of the existence of the nonvanishing dipole moment, characteristic of the conformation of the storage proteins. In other words, the time constants 7, 7r, and 72 are written: [12] 7 = T' exp(-AKE/RT) for calcium ions, sT = rl' exp(-,usE/RT) for acetylcholine, and 72 = 72' exp(-MRE/RT) [13] for the dissociation of AcCh from its receptor, where lK is the Evolution of V, gNa, and gx.…”
Section: B the Chemical Kineticsmentioning
confidence: 99%